2005
DOI: 10.2337/diaspect.18.4.220
|View full text |Cite
|
Sign up to set email alerts
|

Current and Future Treatment of Metabolic Syndrome and Type 2 Diabetes in Children and Adolescents

Abstract: In Brief The metabolic syndrome and type 2 diabetes are occurring at alarming rates in children. Obesity plays an important role in the increased prevalence of its comorbid conditions including dyslipidemia, hypertension,and type 2 diabetes. Lifestyle modification is the mainstay of prevention and treatment for metabolic syndrome and type 2 diabetes; however, it can be costly and labor-intensive. Pharmacotherapy is considered a second line of therapy in adults, but its use in children is controversial. This ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
10

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 67 publications
0
27
0
10
Order By: Relevance
“…The lipid-lowering effects of statins have been accompanied by C IMT regression in children. [Mallare et al 2005]. Ezetimibe is approved for use in children > 10 years of age.…”
Section: Dyslipidemiamentioning
confidence: 99%
See 1 more Smart Citation
“…The lipid-lowering effects of statins have been accompanied by C IMT regression in children. [Mallare et al 2005]. Ezetimibe is approved for use in children > 10 years of age.…”
Section: Dyslipidemiamentioning
confidence: 99%
“…In children the bile-acid binding resins are associated with poor tolerability and low compliance; they also appear to have limited effectiveness in Review achieving lipid-lowering targets. Statins are now recommended as first-line therapy for children aged 10 years and older [McCrindle et al 2007a;Mallare et al 2005]. The age of the youngest patients reported in clinical trials varied from 4 to 10 years old.…”
Section: Dyslipidemiamentioning
confidence: 99%
“…Also, selenium has antioxidant and anti-inflammatory effects and can be effective in diabetes owing to its role in oxidative stress. Studies on diabetes in mice have shown that selenium protects mitochondria from oxidative stress (Akhuemokhan et al, 2013) and plays an important role in the metabolism of vitamin E. It is essential for the normal function of pancreas (Tabar, 2012), Current drugs used for the treatment of diabetes are associated with several side effects such as hypoglycemia, weight gain, gastrointestinal disorders, peripheral edema and impaired liver function (Mallare et al, 2005), hence, there is a need for effective, safe and better oral hypoglycemic agents. According to antioxidant properties of compounds derived from crab shell, the present study was carried out to determine the effects of crab shell hydroalcoholic extract on blood glucose, liver enzymes, NO, antioxidant capacity of serum and histological structure of pancreas in diabetic rats.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] Current treatments for obesity include pharmacotherapy, bariatric surgery, and lifestyle modification. 5 Pharmacotherapy involves the use of anti-obesity drugs such as phentermine and orlistat. 6,7 While each intervention has its distinct advantages, it may also have significant adverse effects and limitations.…”
Section: Introduction Omentioning
confidence: 99%